PERBANDINGAN KINERJA KEUANGAN, STRUKTUR MODAL, DAN NILAI PERUSAHAAN PADA PERUSAHAAN KELUARGA DAN PERUSAHAAN NON-KELUARGA - Rai Rake Setyawan; Adhitya Rechandy Christian (Universitas Ahmad Dahlan, 2022)
This study aims to determine the differences in the financial performance, capital structure, and firm value in family and non-family firms listed on the Indonesia Stock Exchange 2017-2019. The sampling method in this study used purposive sampling technique and data analysis used a pairwise sample methodology by comparing family and non-family firm. The results of this study indicate that there is no difference in finance performance as proxied by sales growth, sales, return on asset (ROA), return on equity (ROE), gross profit margin (GPM), net profit margin (NPM), but there are significant differences in total asset turn over (TATO). The capital structure also shows that there is no difference between the debt to total asset ratio (DAR) and the debt to total equity ratio (DER) proxy, but there is one significant proxy, namely pre-sales working capital and there is no difference in firm value as proxied by earning per share EPS between family and non-family firm.